Review of forensic medicine - Seth, Sumit (Peepee Publishers, 2007)
This book is in the form of points, covering all aspects of Forensic Medicine with extensive chapter wise MCQ bank. It is a must read book for every students aspiring for top ranks in PG Entrance Examination. Its point based approach will help undergraduate students to revise the subject and perform well in Viva Examination. The information is densely packed and can be read in shortest possible time. All information has been checked in standard textbooks like Bernard Knight and Spitz and Fisher. Unique feature of this book is the use of innovative techniques in memorising difficult topics.